(untitled) (Third Sector Social Economic Review, 2022)
With the development of the internet, businesses have begun to communicate with their customers not only in physical environments but also in virtual environments and offer their products and services through internet-based channels. As a result of this change, it has become important for businesses to evaluate the service quality they offer to the customers based on the electronic environment rather than the physical environment. The scales used to measure service quality in the past have been redesigned to measure electronic service quality. Although there are various scales for the measurement of electronic service quality in the literature, it is aimed to determine the validity and reliability of the Turkish version of the E-S-QUAL scale which was developed by Parasuraman, Zeithaml, and Malhotra (2005) to contribute to future studies in this area. The sample of the study consists of 254 students studying in undergraduate programs of Karabük University (N=143) and Çankırı Karatekin University (N=111). To determine the factor structure of the E-S-QUAL scale, exploratory factor analysis was applied and according to the results of the analysis, a four-factor structure was obtained harmoniously the original form of the scale, then this structure was tested with confirmatory factor analysis. It can be said that the four-factor structure of the E-S-QUAL scale, which is compatible with the original, has high reliability and is a valid and reliable measurement tool that can be used in studies in this field to measure electronic service quality.